Beyond retention : cultivating spaces of equity, justice, and fairness for women of color in U.S. higher education - Marina, Brenda Louise Hammett; Ross, Sabrina (Research for social justice., 2016)
In Beyond Retention: Cultivating Spaces of Equity, Fairness, and Justice for Women of Color in U.S. Higher Education, Brenda Marina and Sabrina N. Ross address the continued underrepresentation of women faculty of color at predominantly White colleges and universities through a creative convergence of scholarship focused on intellectual activism and structural change. Inspired by the African American oral tradition of call and response, this text illuminates the calls, or personal narratives of women faculty of color who identify racialized, gendered, sexualized, and class-based challenges associated with work in predominantly White institutions. Accounts of social justice-oriented strategies, policies, and practices that support women faculty of color and reflections by women of color who are senior faculty members serve as literal and metaphorical responses. The convergence of calls for social justice and equity-minded responses and reflections in this text provide intellectual foundations for the development of higher education spaces where women faculty of color can thrive.Beyond Retention is a critical geographic project intended to identify and mitigate structures of oppression that act as barriers to the full incorporation of women of color in predominantly White academic contexts. This text will be of interest to scholars interested in curriculum topics of race, gender, sexuality, and place. The text offers strategies for coping and success for women of color in doctoral programs, faculty positions, and mid-level administration positions within the academy; as such, Beyond Retention will be a valuable addition to the reading libraries of each of these groups. Men and women with interests in the experiences of educators of color within predominantly White contexts will also gain valuable insights from this book, as will individuals interested in various areas of women studies, multicultural education, and diversity.Beyond Retention also provides accounts of practices and policies that have been successful in supporting the needs of women faculty of color; knowledge gained from this text will be useful for higher education administrators seeking to improve the campus climate for faculty of color. Additionally, human resource directors, equal opportunity specialists and diversity trainers will find this text helpful when considering strategies for managing diversity.